The Importance of Continuity of Care Women with Obstetric Trauma - Laktionkinaitė, Ugnė; Stoukuvienė, Žaneta; Liutikienė, Rasa (Slauga. Mokslas ir praktika, 2021)
Around 50% of women who give birth naturally have trauma to the birthing tract requiring soft tissue suturing. In Lithuania, women spend an average of 2-3 days in hospital after an uncomplicated natural delivery, which is not always enough time to acquire the skills to take care of the new-born as well as to care for the delivery wound. Continuity of care after the return of the mother from hospital is particularly important to avoid complications in the postnatal period such as fever, wound infections, resolution of wound edges, incontinence of gases or faeces, formation of fistulae, painful sexual intercourse, and delay of future family planning.Aim of the study: to assess the importance of continuity of care for women with obstetric trauma.Methods: A quantitative study, an anonymous survey of women who have given birth naturally in the last two years and who have experienced various soft tissue injuries of the birthing tract between November 2020 and January 2021, following an analysis of the scientific literature, was conducted.The survey data were analysed using Microsoft Office Excel 2016 data processing software. The study was carried out in accordance with ethical principles.Results: 110 women participated in the study. Most of the respondents were first-time mothers with grade I-II perineal or vaginal tears. More than half of the women highlighted the lack of information from professionals about home care of the birth canal, postnatal sexuality, and family planning.Conclusions: Women with natural childbirth who have suffered soft tissue injuries to the birthing tract experience pain in the wound area in the postnatal period, which limits movement when walking, sitting, getting up from a lying position, and feel anxiety and fear of soft tissue injury when defecating. Mothers are not sufficiently informed about home care of the obstetric wound and would prefer follow-up care in primary care.